Citizen Scientists Help Detect and Classify Dynamically Triggered Seismic Activity in Alaska - Tang, Vivian; Rösler, Boris; Nelson, Jordan; Thompson, JaCoya; van der Lee, Suzan; Chao, Kevin; Paulsen, Michelle (Frontiers in Earth Science, 2020)
In this citizen science project, we ask citizens to listen to relevant sections of seismograms that are accelerated to audible frequencies. The events we are asking citizens to help identify are local seismic events that generate much smaller signals than those associated with the seismic surface waves that might have triggered these local events. The local events include small earthquakes as well as tectonic tremor (series of deep low-frequency earthquakes). While progress has been made in understanding how these events might be triggered by the surface waves from large teleseismic earthquakes around the world, there is no consensus on its physical mechanism. The aim of our project is to receive the help of citizens to increase general knowledge of when and which triggered seismic events occur or not occur during transient strain events, such as from propagating surface waves. A better understanding of such triggered seismic events is expected to provide important clues towards a fundamental understanding of how earthquakes nucleate and how large earthquakes might interact with small ones. From the citizens’ classifications we determined that citizen scientists achieve a higher reliability in detecting earthquakes and noise than in detecting tremor or other signals and that citizen scientists more accurately identified earthquake signals than a trained machine-learning algorithm. For tremor classifications we depend entirely on the citizens as no machine has yet learned to detect tremor.